HEAT TREATMENT FOR THE PRECOOCKED SHRIMPS PRODUCTION: VIBRIO PARAHAEMOLYTICUS RISK ANALYSIS - C Ercolini; A. Terarolli; L. Serracca; F. Gallo; M. Prearo; M Orlandi; M. Imberciadori (Italian Journal of Food Safety, 2013)
Vibrio parahaemolyticus is a common microflora of marine and estuarine waters known to be associated with gastroenteritis due to consumption of raw seafood, cooked food contaminated through direct contact (cross contamination) or improperly cooked. The aim of this study was to evaluate the effectiveness of two different heat processes in reducing microbial load of V. parahaemolyticus. Data show a 4 Log10/g reduction of bacterial load after 3,30 and 15 minutes at 95 °C.